1988
DOI: 10.1128/jcm.26.1.38-40.1988
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of capsular polysaccharide types 5 and 8 among Staphylococcus aureus isolates from cow, goat, and ewe milk

Abstract: Monoclonal antibodies to Staphylococcus aureus capsular polysaccharide types 5 and 8 were used to serotype by enzyme-linked immunosorbent assay 212, 54, and 33 isolates from cow, goat, and ewe milk, respectively. Capsular types 5 and 8 accounted for 69.4% of bovine isolates and 71.5 and 78.8% of goat and ewe isolates, respectively. Type 5 was predominant in strains from bovine sources (51.4%), whereas type 8 was prevalent in strains from caprine (68.5%) and ovine (75.8%) sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
1
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 14 publications
4
65
1
1
Order By: Relevance
“…In contrast, type 5 and 8 strains are the predominant isolates which account for approx. 80% of recent isolates from all sources (Albus et al, 1988;Arbeit et al, 1984;Hochkeppel et al, 1987;Karakawa and Vann, 1982;Karakawa et al, 1985;Poutrel et al, 1988;Sompolinsky et al, 1985). These strains produce a small amount of capsule and are therefore referred to as 'microencapsulated' (Wilkinson, 1983). S. aureus M, isolated from an infected human-hand laceration, is a type 1 capsule producer (Scott, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, type 5 and 8 strains are the predominant isolates which account for approx. 80% of recent isolates from all sources (Albus et al, 1988;Arbeit et al, 1984;Hochkeppel et al, 1987;Karakawa and Vann, 1982;Karakawa et al, 1985;Poutrel et al, 1988;Sompolinsky et al, 1985). These strains produce a small amount of capsule and are therefore referred to as 'microencapsulated' (Wilkinson, 1983). S. aureus M, isolated from an infected human-hand laceration, is a type 1 capsule producer (Scott, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of capsular polysaccharides in vitro and in vivo (POUTREL et al 1988;JOHNE et a]., 1989;SUTRA et al, 1990) and pseudocapsules (WATSON and FRANKLIN, 1988) has been reported. Although the relationship between these surface structures and those expressed in serum-soft media is not fully understood (SUTRA et al, ), JOHNE et al (1989 found a correlation between presence of exopolysaccharides in vivo and D C M in Staphylococcus medium 110 (agar 1.5 "A) in S. aureus cultured directly from milk.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct surface components have been detected in Staphylococcus aureus isolated from bovine milk using tests that showed a good correlation with encapsulation (YOKOMIZO et al, 1977;POUTREL et al, 1988;WATSON and FRANKLIN, 1988). These structures have been defined as capsules (YOKOMIZO et al, 1977;OPDEBEECK and NORCROSS, 1983), microcapsules (SOMPOLINSKY et al, 1985) and pseudocapsules (WATSON and FRANKLIN, 1988) and have been typed using different serological methods.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of S. aureus causing bovine mastitis, the expression of a polysaccharide capsule has long been debated and different definitions have been suggested by several investigators. Poutrel et al (12) reported that S. aureus strains isolated from cow, goat and ewe (4) reported that S. aureus strains isolated from ruminant mastitis produce a loose exopolysaccharide structure in vivo defined as slime. After a similar study, Sutra et al (15) also reported that the majority of S. aureus strains isolated from the milk of cows with mastitis tested reacted with capsular type 5 and 8 antibodies.…”
Section: Staphylococcusmentioning
confidence: 99%